GPS network for deformation control in the Mount Melbourne area (Antarctica): preliminary results of third measurements campaign - O. Al Bayari; A. Capra; L. Vittuari; RADICIONI, Fabio (Nautilus, 1996)
GPS network has been estabilished in the Mount Melbourne Volcano area (Antarctica) for crustal deformation control. The network was installed in 1988-89 Italian Expedition in Antarctica by Prof. A. Gubellini and Prof. D. Postpischl. Successively was surveyed three times: 1990-91, 1993-94 and 1995-96. The preliminary results of third measurements campaign and the comparison with the previous surveys are here presented.